Konsep Kafarat dalam Perkawinan: Rekonstruksi Perjanjian Perkawinan dalam Pemikiran Prof. Fathorrahman: The Concept of Kafarat in Marriage: A Reconstruction of the Prenuptial Agreement in the Thought of Prof. Fathorrahman - Nurul Firdaus; Fathurrahman Alfaraqy; Hammad Farobi Syahuda (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Marriage agreements in Indonesia, as regulated under Article 29 of Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 and further expanded through Constitutional Court Decision Number 69/PUU-XIII/2015, aim to provide legal certainty regarding the management of assets and the responsibilities of spouses. However, their effectiveness remains limited due to the absence of direct sanctions in the event of non-compliance. This study examines the legal position of marriage agreements in Indonesian law, analyzes the concept of kafarat in Islamic jurisprudence as formulated by Prof. Dr. Fathorrahman, and reconstructs it as a religious-legal sanction aligned with human rights principles. Using a qualitative-descriptive approach through library research and interviews, the findings indicate that kafarat, in both material and immaterial forms, may serve as a more effective enforcement mechanism with preventive and restorative functions, while remaining consistent with principles of equality, non-discrimination, and human dignity. Consequently, the reconstruction of kafarat presents a transformative legal model that strengthens the binding force of marriage agreements and contributes to the development of Islamic family law in Indonesia.